Socioeconomic differences in hospital care use for stroke and ischaemic heart disease in the China Kadoorie Biobank study - Levy, M (2021)
The rapid economic, demographic, and epidemiologic transitions that occurred in China in recent decades have increased the burden of non-communicable diseases, including cardiovascular diseases (CVD), as well as health expenditures and health inequalities. In 2009, China launched major healthcare reforms to provide equal and affordable basic healthcare for all by 2020.